Hospitalidade sob o olhar do hóspede nos espaços do hotel - Przybylski, Inês Machado (My University, 2014)
Dissertation presented to the Caxias do Sul University, RS, on the Program of Master Post-graduation in Tourism, line of research "Tourism and Organizations", as partial requisite for attainment of the heading of Master in Tourism. The research had focus in the guest´s perception on hospitality, to know if it´s related to the human contact decurrently in the treatment of the collaborators who pay service on the different hotel areas. The study´s theoretical reflections were headed on the themes hospitality and fundamental reception, considering the terms´ wide areas, the senses and meanings found in specific literature. The study researched the guests´ opinions about the concept of hospitality, on a four-star classified, luxury pattern hotel. On a quantityquality methodology, was given to the Grande Hotel Dall´Onder´s guests, in Bento Gonçalves, RS, throughout December month, 2007, 141 questionnaires, concerning the guest´s opinion on if hospitality relates to contact with people in different environments, or if only spaces can be related to hospitality. The results shown that there is the sense of hospitality, even without the presence of another person, because someone already prepared the room for them. The research also indicates that, the sectors that keep professionals working were elected from the guests, among the ones who give the most sense of hospitality; therefore, from the guest´s view, hospitality is connected with human touch, even when there´s not human contact. Throughout bibliographical revision, were search the necessary components, for the hospitality relations to happen, from where were selected to study, two actors the guest and the host and the space where the meeting happens, the hotel.
Dissertação apresentada ao Programa de Pós-Graduação Mestrado em Turismo da Universidade de Caxias do Sul/RS, na linha de pesquisa "Turismo e Organizações", como requisito parcial para obtenção do título de Mestre em turismo. O problema da investigação teve como foco, averiguar a percepção do hóspede com respeito à hospitalidade para saber se ela está relacionada ao contado humano decorrente do atendimento dos colaboradores que prestam serviços nos diferentes espaços do hotel. As reflexões teóricas do estudo estiveram voltadas aos temas hospitalidade e acolhimento fundamentalmente, considerando as abrangências dos termos, dos sentidos e significados que se encontra na literatura especializada. O estudo investigou a opinião dos hóspedes a respeito de hospitalidade, em um hotel classificado com quatro estrelas, padrão luxo. Sob uma metodologia quanti-qualitativa, foram aplicados 141 questionários aos hóspedes do Grande Hotel Dall Onder, na cidade de Bento Gonçalves, R.S., no decorrer do mês de Dezembro de 2007, visando saber se estes relacionam a hospitalidade aos contatos com pessoas nos diferentes ambientes ou se, para eles, somente os espaços podem denotar hospitalidade. Os resultados apontaram que existe a percepção da hospitalidade, mesmo sem a presença de outras pessoas, pois, subentendem os respondentes, que alguém já preparou, antecipadamente, o local. A pesquisa também apontou que, os setores que mantêm profissionais atuando, são os elencados pelos hóspedes como de hospitalidade mais perceptível; portanto, pela ótica do hóspede, a hospitalidade está ligada ao contato humano, mesmo que não seja este contato, presencial. Através de revisão bibliográfica, buscaram-se quais os componentes necessários para que aconteçam as relações de hospitalidade, de onde foram selecionados para estudo, dois atores o hóspede e o anfitrião - e o espaço onde ocorre o encontro, o hotel.
Keywords: TURISMO; Turismo; Hospitalidade; Hóspedes; Espaço; Hotéis; Tourism; Hospitality; Guests; Space; Hotel